The Social Construction of Indian Forests - Jeffery, Roger, (Brill | Manohar Publishers & Distributors, 2024)
The meanings of Indian forests have been contested for many years. Even before the British colonial period, forests were seen as the haunts of outlaws, the source of beautiful images, the abode of holy men, as reserves for hunting as well as potential resources for exploitation. The Social Construction of Indian Forests explores these meanings, and draws out their relevance in diverse settings, from political party imagery in Tamil Nadu, through the Bengali novel, the management of wildlife reserves, the significance of the devarakadus (sacred groves) of Karnataka and the social meaning of forests in Uttarakhand, to case studies of Jharkhand and Karnataka in the new attempts to promote participation with Non-Governmental Organisations in the management of India's state forests.